Saringgong: An Alternative Media for Slow Learner Students in Learning Mathematics - Anny Sovia; Yulyanti Harisman; Ronal Rifandi (Department of Mathematics, Universitas Negeri Padang (UNP), 2022)
The purpose of this study is to describe the traditional Indonesian game (namely Saringgong) as a medium for slow learner students in learning mathematics. Saringgong is a game that utilizes gravels as a medium. This research is a descriptive study with a qualitative approach, the method that used is ethnography. Data were collected by using ethnographic principles, such as interviews, observations, documentation, and field notes. The results of this study illustrate that the traditional game Saringgong can be used as an alternative learning medium for Slow Learner students to practice numeracy skills, increase focus and motivation of students in learning mathematics.